2003
DOI: 10.1088/0268-1242/18/6/335
|View full text |Cite
|
Sign up to set email alerts
|

Semi-insulating porous SiC substrates

Abstract: Semi-insulating SiC substrates were fabricated on a base of porous silicon carbide made from 4H and 6H commercial SiC wafers. Porous SiC (PSC) layers, 3 µm in thickness, were made by surface anodization of SiC wafers and then impregnated with excessive Si from a sputtered SiO 2 film during thermal processing at 1200 • C. The processed structures were studied by Auger electron spectroscopy (AES), secondary ion mass spectroscopy (SIMS) and x-ray photoelectron spectroscopy (XPS). The Si/C ratio in the processed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Diffusion in SiC is believed to proceed mostly via kickout or vacancy-related mechanisms [1][2][3][4][5]. Vacancies define many physical properties of SiC [7,8], and one of the current subjects of research is their contribution to the formation and properties of porous SiC, a material with many prospective applications [9,10]. The very formation of porous structure in SiC is believed to proceed via vacancy migration and clustering [11], and there are all grounds to believe that experimentally observed modification of the structure under thermal annealing [12,13] is also due to vacancy redistribution.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion in SiC is believed to proceed mostly via kickout or vacancy-related mechanisms [1][2][3][4][5]. Vacancies define many physical properties of SiC [7,8], and one of the current subjects of research is their contribution to the formation and properties of porous SiC, a material with many prospective applications [9,10]. The very formation of porous structure in SiC is believed to proceed via vacancy migration and clustering [11], and there are all grounds to believe that experimentally observed modification of the structure under thermal annealing [12,13] is also due to vacancy redistribution.…”
Section: Introductionmentioning
confidence: 99%
“…First of all blue emission had been investigated in PSiC layers [1]. Latter it was shown that PSiC is a promising medium for diffusion, which allows one to control electrical properties of bulk SiC material using diffusion doping [2]. Some prospective applications of SiC-based homoepitaxial device structures formed on PSC substrates with improved quality were reported [3].…”
Section: Introductionmentioning
confidence: 99%
“…Porous SiC (PSiC) has been around for a number of years as an object of interest for developing new technologies and applications. It has been shown that porous SiC is a promising medium for diffusion, which allows one to control electrical properties of bulk SiC material using diffusion doping [1]. Some perspective applications of SiC-based homoepitaxial device structures formed on PSiC substrates with improved quality were reported [2].…”
Section: Introductionmentioning
confidence: 99%